Synthesis and Evaluation of Phenyliminoindolin-Containing Phenylacetamide Derivatives with the Antidepressant and Anticonvulsant Effects - Guan, Li-Ping; Liu, Bing-Yu; Quan, Ying-Chun; Yang, Li-Ye; Zhen, Xing-Hua; Wang, Si-Hong (Medicinal Chemistry, 2016)
Background: To discover a novel antidepressant-like effect and anticonvulsant compound, seventeen new 2-oxo-3-phenyliminoindolin-1-Nphenylacetamide compounds were synthesized and screened for the antidepressant activity and anticonvulsant effects. Method: 2-oxo-3-phenyliminoindolin-1-N-phenylacetamide derivatives were synthesized with indoline-2, 3-dione as the starting material, through a nucleophilic substitution reaction and a nucleophilic addition-elimination reaction. The target derivatives 2a-2q were evaluated the antidepressant-like activity using the FST, TST, and evaluated anticonvulsant effect by MES test. The main monoamine neurotransmitters and their metabolites in mouse brain regions were also simultaneously determined by HPLC-ECD. Results: It was observed that 13 compounds showed significant reductions in the immobility time in the FST at a concentration of 50 mg/kg. Compound 2b was found to have the most potent antidepressant activity in the FST and the TST for 30 min after treatment. Compound 2b significantly increased the concentrations of the main neurotransmitters 5-HT, NE and the metabolite (5-HIAA, suggesting that the effects of compound 2b may be mediated through these neurotransmitters. As assessed using maximal electroshock, 13 compounds showed the anticonvulsant effects administered at the concentration levels of 100 or 300 mg/kg. Compound 2b showed anticonvulsant effect. Compound 2b could potentially be used as adjuncts of the antidepressants to treat depression in patients with epilepsy. Conclusion: In conclusion, compound 2b produced significant antidepressant-like activity and the mechanism of action may be due to increased 5-HT and NE in the mouse. Compound 2b showed more anticonvulsant effect. Compound 2b could potentially be used as adjuncts of the antidepressants to treat depression in patients with epilepsy.
Keywords: Phenyliminoindolin-N-phenylacetamide